Alterations of gut mycobiota profiles in intrahepatic cholangiocarcinoma - Zhang, Lilong; Chen, Chen; Chai, Dongqi; Kuang, Tianrui; Deng, Wenhong; Wang, Weixing (Frontiers in Microbiology, 2023)
Objective Intrahepatic cholangiocarcinoma (ICC) is a silent liver malignancy with an increasing incidence. Gut mycobiota plays a crucial role in benign liver diseases; however, its correlation with ICC remains elusive. This study aimed to elucidate fungal differences in patients with ICC compared to healthy controls. Methods The 40 fecal samples from 23 ICC patients and 17 healthy controls were collected and analyzed using ITS2 rDNA sequencing. Obtaining the OTUs and combining effective grouping, we carried out the biodiversity and composition of the fungi, as well as FUNGuild functional annotation. Results Our results revealed the presence of intestinal fungal dysbiosis with significant enrichment of opportunistic pathogenic fungi such as Candida and C. albicans, and significant depletion of the beneficial fungus Saccharomyces cerevisiae in ICC patients compared with healthy controls. Alpha-diversity analysis demonstrated that patients with ICC showed decreased fungal diversity compared to healthy controls. Beta diversity analysis indicated that the two groups exhibited significant segregated clustering. Besides, C. albicans was found to be significantly more abundant in the ICC patients with TNM stage III-IV than those with stage I-II. The FUNGuild functional classification predicted that pathotrophs were the most abundant taxon in the ICC group, well above their abundance in healthy controls. Conclusions This study indicates that dysbiosis of the fecal mycobiome might be involved in ICC development. Further research into gut fungi may contribute to new therapeutic options for ICC patients.